STUDENT'S VISUAL REASONING IN SOLVING LINEAR EQUATIONS IN TERMS OF LEARNING STYLE - Indah Dwi Utami; Masduki Masduki (Prima: Jurnal Pendidikan Matematika, 2023)
This study aims to describe students' visual mathematical reasoning abilities based on visual learning styles, auditory, and kinesthetic (VAK) in solving systems of linear equations. The research approach used is qualitative with a case study design. The research subjects involved were 30 students of class VIII at a private school in Surakarta. The research instrument used was a VAK learning style questionnaire, visual reasoning test (TPV) questions, and interview guidelines. Data analysis was carried out inductively, namely data collection, data reduction, data presentation, and drawing conclusions. The results showed that there was a diversity of students' reasoning abilities based on learning styles. Although visual and auditory students are able to present mathematical expressions in visual form in the form of graphs, their ability to describe graphs is relatively diverse. In other words, visual and auditory students have various abilities on various investigative indicators. Meanwhile, students with kinesthetic learning styles cannot present mathematical expressions in the form of graphs so they cannot describe visual objects. In other words, kinesthetic students are not able to fulfill the investigation indicators. Thus, it can be concluded that the visual reasoning ability of the kinesthetic student's investigative dimension is the weakest compared to the visual and auditory learning styles. Meanwhile, the dimensions of student investigation with visual and auditory learning styles are relatively diverse.